CANINE (К9) SUPPORT OF THE ACTIVITIES OF THE STATE CUSTOMS SERVICE OF UKRAINE (Bulletin of criminological association of Ukraine, 2025)
The article analyzes the regulatory and legal support for the activities of canine units of the State Customs Service of Ukraine. Particular attention is paid to the standardization of work and mechanisms for involving canine teams in the implementation of the tasks of the State Customs Service of Ukraine in the field of combating smuggling and ensuring the proper implementation of customs control. The features of the training and activity of service dogs are determined, which distinguish the state and level of canine support of the activities of customs authorities from the canine support of other law enforcement agencies. It is emphasized that the development of technologies is not able to compete with the abilities of service dogs, which currently remain the most effective and efficient means of detecting facts of illegal movement of goods across the state border. It is also noted that, unlike other law enforcement agencies, the activities in the field of canine support in the State Customs Service of Ukraine, among other things, arefocused on the service dog, which acts as a «partner» in the «canine handler-dog» relationship. It is emphasized that the burden on canine teams currently remains a problematic issue, which is primarily related to the legal regime of martial law.
Keywords: canine support of customs authorities; К9; State Customs Service; canine team; customs control; combating offenses; violation of customs rules; smuggling